Prevalence, demographic factors, co-morbidities, and treatment types associated with acanthosis nigricans in a large cross-section of 900+ transmasculine patients: Data from a single academic center 2016–2023 - Twan Sia; Farah Abou-Taleb; Connie Ma; Shufeng Li; Anne Lynn S. Chang (PLoS ONE, 2026)
Background Acanthosis nigricans (AN) is a highly visible cutaneous condition that has been associated with cardiometabolic factors, drugs, or malignancy in various populations. AN can be challenging to treat. Transmasculine patients are a special population, but their AN prevalence, and whether AN associates with demographic factors, co-morbidities and gender affirming care (GAC) treatment types have not been well-studied. Our study explores whether GAC treatment type is associated with AN while controlling for confounders in a large group of transmasculine patients at an academic center. Methods Following Institutional Review Board approval, the Stanford Research Repository (01/01/2016–21/09/2023) was searched to identify transmasculine patients for individual chart review. The primary outcome was AN and its association with demographic factors, co-morbidities, and gender-affirming care (GAC) treatment type by multivariate logistic regression (presented as Odds Ratio (OR) and 95% Confidence Interval (CI)). Results Out of 945 transmasculine patients, AN prevalence was 4.55%, an elevated rate compared to the overall database prevalence of 0.3% for the same period. Prevalence of AN in transmasculine patients never exposed to GAC was 4.02% (7/174). Median age was 20.1 years (interquartile range (IQR) 17.2–25.4). On multivariate logistic regression, AN was associated with obesity (OR 9.31, 95% CI 4.40–20.33), metabolic syndrome (OR 4.04, 95% CI 1.09–15.23), prediabetes (OR 3.17, 95% CI 1.10–8.54), hypertension (OR 2.74, 95% CI 0.96–7.18), and Hispanic ethnicity (OR 2.46, 95% CI 1.12–5.25). GAC type (including exogenous testosterone usage) was not associated with AN, despite >99% power to detect a 10% difference in AN prevalence. Conclusions Because AN is enriched in transmasculine patients, and precedes co-morbidities in a majority of cases, dermatologists and other physicians should consider examination of common areas for AN in in transmasculine patients, as screening and diagnosis of co-morbidities could lead to improved health outcomes.